OPTIMASI TAKARAN KACANG KORO PEDANG PUTIH (Canavalia ensiformis (L) SEBAGAI BAHAN BAKU PEMBUATAN YOGHURT - R. Suryaningrum; Pungky Slamet Wisnu Kusuma (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2013)
Sword white lentils (Canavalia ensiformis (L) have hight potential to be used as raw material for food processing products. Study aimed to find optimum sword white lentils dose as raw material for yoghurt. Study have conducted using a completely randomized experimental design consisted of 5 doses of lentils (333, 250, 200, 167 and 143 g/l medium) with 4 replication. Fermentation procces have conducted using Lactobacillus bulgaricus and Streptococcus thermophilus 1:1 in ration for 12 h. Results showed dose of lentils significant effect (P <0.05) on bacterial counts, levels of carbon and nitrogen, and viscosity and organoleptic properties of yogurt. Bacterial count, Levels of carbon and nitrogen as well as yogurt highest viscosity obtained at doses lentils 333 g/l. Nevertheless, the organoleptic properties of yogurt were most preferred by the panelists obtained at doses lentils 200 g/l. Study conclude sword white lentils can be used as raw material for making yoghurt with the best dosage is 200 g/l medium. Key words: lentils, Lactobacillus bulgaricus, Streptococcus thermophilus, yoghurt